Application of SPOC flip classroom based on WeChat platform in clinical pharmacology teaching - YU Yan, SHEN Bing-zheng (Jichu yixue yu linchuang, 2020)
Objective To explore the application of SPOC flipped classroom based on WeChat platform in clinical pharmacology teaching. Methods The undergraduates, who took the course in the same grade majored in clinical medicine from the first clinical college of Wuhan University, were divided into the control group using traditional teaching methods and the experimental group adopting the SPOC flip classroom teaching method based on the WeChat platform. Results The theoretical test score(83.39±9.17) of the experimental group, which was significantly higher than the control group (76.91±9.70) (P＜0.05). For the examination of abbreviated question and case analysis with a score of 40 points, the score of experimental group (31.61±3.69) was higher than the control group (26.68±5.15) (P＜0.001). Conclusions The application of the SPOC flip classroom based on WeChat platform in teaching clinical pharmacology for the undergraduate students can improve their performance, especially the capacity to use the theoretical knowledge to solve clinical problems.